Working with circus artists: Reflections on a process of collaborative research, participation and commitment - Infantino, Julieta Lorena (2018)
The purpose of this article is to share some reflections on the long research experience I have developed with circus artists in the City of Buenos Aires, Argentina. These reflections revolve around the question on the contributions of social sciences, particularly anthropology, through research practices conducted in collaboration with artists. I am interested in rethinking the role of the researcher by understanding science from a conception in which commitment, collaboration, and participatory knowledge building can potentiate research practices and, at the same time, create dilemmas and challenges. What are the theoretical-methodological implications of the roles we can play throughout a long lasting research process? What are the tools we can use when conducting research on the fields we also participate in, socially and politically? How can we synchronise academic and reflection times with action times?